2014
DOI: 10.2147/ijwh.s40889
|View full text |Cite
|
Sign up to set email alerts
|

Refractory fallopian tube carcinoma – current perspectives in pathogenesis and management

Abstract: Fallopian tube carcinoma (FTC) is considered a rare malignancy, but recent evidence shows that its incidence may have been underestimated. Risk-reducing salpingo-oophorectomy (RRSO) in breast cancer susceptibility gene (BRCA)-positive women has provided a unique opportunity to study the pathogenesis of FTC and ovarian carcinomas. Newer data now suggest that most high-grade serous cancers of the ovary originate in the fimbrial end of the fallopian tube. Due to the presumed rarity of FTC, most current and more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…PFTC and EOC bear clinical and histological resemblance, although the former recurs in retroperitoneal nodes and distant sites more often than the latter [ 15 , 16 , 17 ]. Treatment of PFTC is similar to that of EOC, and it includes a total abdominal hysterectomy and omentectomy, followed by adjuvant taxane- and platinum-based chemotherapy, as well as radiotherapy [ 18 , 19 , 20 , 21 , 22 , 23 ]. Previous studies suggested that patients with serous PFTC are eligible for clinical trials designed for those with serous EOC [ 3 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PFTC and EOC bear clinical and histological resemblance, although the former recurs in retroperitoneal nodes and distant sites more often than the latter [ 15 , 16 , 17 ]. Treatment of PFTC is similar to that of EOC, and it includes a total abdominal hysterectomy and omentectomy, followed by adjuvant taxane- and platinum-based chemotherapy, as well as radiotherapy [ 18 , 19 , 20 , 21 , 22 , 23 ]. Previous studies suggested that patients with serous PFTC are eligible for clinical trials designed for those with serous EOC [ 3 , 24 ].…”
Section: Introductionmentioning
confidence: 99%